Meanings about the doctor-patient relationship in the family health strategy: Thoughts on health care from the perspective of the users. - Marcelo Pereira de Brito; Eunice Nakamura (Social Medicine Publication Group, 2021)
Primary Health Care (PHC) appears as the main guideline for health actions in the Family Health Strategy (FHS). Its prerogatives include multidisciplinary teamwork focused on the users, families and communities where this strategy is inserted. However, the historical context of health practices in Brazil has shown that PHC does not consolidate in the country without contradictions. Some of its principles, such as completeness, arise in the clinical encounter between physicians and patients still strongly marked by the asymmetric relationship, by biomedical discourse and practice. The aim of this study was to analyze and understand some of the meanings present in the doctor-patient relationship, from the perspective of the users, with follow-up and observation of meetings of a team from the FHS unit in the Areia Branca neighborhood, of Santos-SP; and in-depth interviews, with a semi-structured script, with five users served by this team. Thus, in the interpretation of the meanings of the doctor-patient relationship, attributes related to familiarity, trust and longitudinality permeated by processes of symbolic resignification of the medical discourse by the users, presenting components related to the autonomy of the interviewees in dealing with their health-disease processes.